Integration of extracellular RNA profiling data using metadata, biomedical ontologies and Linked Data technologies. Issue 1 (28th August 2015) - Subramanian, Sai Lakshmi; Kitchen, Robert R.; Alexander, Roger; Carter, Bob S.; Cheung, Kei‐Hoi; Laurent, Louise C.; Pico, Alexander; Roberts, Lewis R.; Roth, Matthew E.; Rozowsky, Joel S.; Su, Andrew I.; Gerstein, Mark B.; et al.
Abstract : The large diversity and volume of extracellular RNA (exRNA) data that will form the basis of the exRNA Atlas generated by the Extracellular RNA Communication Consortium pose a substantial data integration challenge. We here present the strategy that is being implemented by the exRNA Data Management and Resource Repository, which employs metadata, biomedical ontologies and Linked Data technologies, such as Resource Description Framework to integrate a diverse set of exRNA profiles into an exRNA Atlas and enable integrative exRNA analysis. We focus on the following three specific data integration tasks: (a) selection of samples from a virtual biorepository for exRNA profiling and for inclusion in the exRNA Atlas; (b) retrieval of a data slice from the exRNA Atlas for integrative analysis and (c) interpretation of exRNA analysis results in the context of pathways and networks. As exRNA profiling gains wide adoption in the research community, we anticipate that the strategies discussed here will increasingly be required to enable data reuse and to facilitate integrative analysis of exRNA data.